APLIKASI PENGELOLAAN TRANSAKSI RESERVASI PADA HOTEL MANGKUTO PAYAKUMBUH DENGAN TEKNOLOGI WAP - Novi Yona Sidratul Munti (Jurnal Inovasi Teknik Informatika, 2021)
The development of database technology cannot be separated from the development of software and hardware, one of the popular software development applications is WAP. where the latest programming language WAP is designed to be able to take advantage of the facilities available in Windows and is software that is commonly used to create programs that are quite simple but have a lot of scope that can be done. The use of the WAP programming language in the use of databases is a technological advance in the development of databases and other applications that can directly relate to computers. In handling large data, the WAP program is very effective compared to manual processing systems that are carried out or with programs that are accessed via a mobile phone. By using WAP this activity is intended to create a hotel database program with a server system that is used to monitor all administrative activities.